TRIMATRA UNTUK MEMENANGKAN PERSAINGAN: VALUE, KUALITAS JASA, DAN DELIGHT - Amalia, Sholihati; Raharso, Sri (Universitas Muhammadiyah Surakarta, 2008)
Emulation level which progressively tightened to cause every organization should be able to give superior value to customer. Organization should be able to give the service quality such as those which wanted by the customer, not solely pursuant to specification of organization. If this matter happened, hence customernot even fulfilled its requirement, farther customer will feel delight. Outcome of delight customer is customer loyalty.